Temporal Metaphors as a Linguistic Phenomenon: Conceptual Frameworks across Different Languages - Huszka, Dr. Balazs; Stark, Dr. Alexander; Haji Ya’akub , Hajah Zurinah; Haji Abd Rahman, Nur Ezzati Rasyidah; Robita Ika Annisa (Talenta Publisher, 2025)
Metaphors are not merely decorative linguistic devices but play a significant role in shaping cognition and cultural understanding. The influence of linguistic background on thought processes is central to the Sapir-Whorf Hypothesis, which posits that language shapes cognitive perception and cultural behaviour. This study aims to explore the relationship between language and cognition through the lens of temporal metaphors. By examining linguistic frameworks across diverse cultures, the research seeks to demonstrate how temporal metaphors influence cognitive processes, cultural practices, and perceptions of time. A qualitative approach was employed, synthesising theoretical and empirical literature on metaphor, linguistic relativity, and temporal cognition. The analysis focused on case studies from languages such as English, Mandarin, Hopi, and Aymara, highlighting both universal and culturally specific temporal metaphors. The study reveals that temporal metaphors vary significantly across languages, reflecting unique cultural perspectives while exhibiting shared cognitive patterns. For instance, English and Mandarin conceptualise time through horizontal and vertical orientations, respectively, while Hopi and Aymara temporal frameworks challenge conventional Western notions. The findings support the weaker form of the Sapir-Whorf Hypothesis, showing that language influences thought without rigidly determining it. Furthermore, the research demonstrates that temporal metaphors are essential cognitive tools, shaping abstract concepts and influencing behaviour across cultural contexts.